2002
DOI: 10.1016/s0736-0266(01)00094-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different exposures of hyperbaric oxygen on ligament healing in rats

Abstract: Hyperbaric oxygen (HBO) is a method of augmenting, intermittently, oxygen availability to tissues. We examined the effect of three different HBO exposures on the healing of experimentally induced ligament lacerations in the right hind limb of 44 male Wistar rats. Animals were divided into four groups after ligament injury: (a) control group, animals breathed room air a t 1 ATA (atmosphere absolute) in a hyperbaric chamber for 60 min; (b) HBO treatment at 1.5 ATA for 30 rnin once a day, (c) HBO treatment at 2 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 16 publications
(19 reference statements)
4
30
0
1
Order By: Relevance
“…28 Prolonged hypoxia could be a major factor in the impaired production of cartilaginous callus in smokers, since oxygen is essential for physiologic hydroxylation of proline and lysine, a critical step in type II collagen synthesis. 29 Jorgensen et al demonstrated decreased hydroxyproline concentrations at a site of wound healing in smokers compared to nonsmokers, indicating decreased collagen synthesis in the smoking group. 30 Decreased or delayed type II collagen synthesis as a result of smoking and tissue hypoxia could directly lead to the deleterious effects of smoking on fracture healing.…”
mentioning
confidence: 98%
“…28 Prolonged hypoxia could be a major factor in the impaired production of cartilaginous callus in smokers, since oxygen is essential for physiologic hydroxylation of proline and lysine, a critical step in type II collagen synthesis. 29 Jorgensen et al demonstrated decreased hydroxyproline concentrations at a site of wound healing in smokers compared to nonsmokers, indicating decreased collagen synthesis in the smoking group. 30 Decreased or delayed type II collagen synthesis as a result of smoking and tissue hypoxia could directly lead to the deleterious effects of smoking on fracture healing.…”
mentioning
confidence: 98%
“…The effects of HBO 2 therapy on soft tissue injuries during sports activities, including sprains, 2 ligament injuries, [3][4][5] contusions, and muscle strains, [6][7][8][9][10] have been widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Further, there has been some thought that MENS combined with icing might be a useful therapy for sports-related skeletal muscle injuries 3) . Hyperbaric oxygen (HBO) therapy is known to facilitate repair of damaged tissue [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . With HBO, pure oxygen is administered in a high pressure environment of 2.0 or more atmospheres absolute (ATA) for 60 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…In general, HBO is considered to be applicable to emergency conditions (carbon monoxide poisoning, severe infection, compartment syndrome, for example) and to non-emergency conditions (refractory ulcer, skin graft, chronic refractory osteomyelitis, for example) 33)34) . There have been numerous reports indicating that HBO facilitates the regeneration of soft tissue [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] , and this includes the regeneration required in cases of skeletal muscle injury [19][20][21][22][23][24] . The beneficial effects of HBO have been reported in relation to various specific sports injuries 21)22) [25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%